Attachment patterns and separation anxiety symptom - Mofrad, Sakineh; Abdullah, Rohani; Uba, Ikechukwu (Canadian Center of Science and Education, 2010)
Literature suggests that child attachment and anxiety symptoms are related. One purpose of the present study was to assess whether attachment patterns related differently to separation anxiety symptoms (fear of being alone, and fear of abandonment). Three attachment patterns assessed were secure, avoidant and ambivalent attachment. Findings indicated that ambivalent attachment was most consistently related with higher separation anxiety symptom. And also, different associations were found between the three patterns of attachment and separation anxiety symptoms. In conclusion, those mothers who were consistently responsive and supportive are more responsible for the child’s health.